explain why 1/((sqrt3)-1) = 1/((sqrt3)-1) x ((sqrt3) +1)/((sqrt3) +1)
i think the obvious answer is that ((sqrt3) +1)/((sqrt3) +1) = 1 but i dont know if thats the answer im supposed to be looking for...
explain why 1/((sqrt3)-1) = 1/((sqrt3)-1) x ((sqrt3) +1)/((sqrt3) +1)
i think the obvious answer is that ((sqrt3) +1)/((sqrt3) +1) = 1 but i dont know if thats the answer im supposed to be looking for...
That's exactly the reason. If you multiply a number by 1, you get what you started with.
And from here, you can rationalise the denominator.